(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
A new educational reform runs through all foreign teaching courses, including audio-visual, speaking, reading, writing, and translating practices, in light of the significant, constant renovation and development of various knowledge and economy; talents of the compound, high quality, and heightened skills are urgently needed in society. Films (DVD, Mp3, etc.) play a vital role in foreign language labs in China using computers. More and more students are taking an interest in language acquisition, not just in learning new words or phrases or dialects or dialects or dialects. Now, students are getting more and more eager to learn new things and better understand the process of learning a new language. Because of this, foreign teachers face enormous challenges: First, how to turn audio-visual classrooms into a helpful teaching tool rather than just a kind of class amusement; and second, ways of getting students involved in class discussions and debates. How can this be done in a classroom setting when teaching listening and speaking skills to students? Helping children gain self-assurance in their ability to deal with the language can be a difficult task. How can classroom processes be designed based on student listening and speaking ability? For that reason, the objective of this paper is to provide students with some valuable and practical ways for increasing their level of self-confidence while learning English.